An Efficient Forward-Biased Si CMOS LED With High Optical Power Density and Nonlinear Optical-Power-Current Characteristic - Jia Cong; Luhong Mao; Rong Xie; Sheng Xie; Weilian Guo (IEEE Photonics Journal, 2019)
A forward-biased silicon-based light-emitting device (Si-LED) was designed and fabricated by standard 0.18 μm complementary metal-oxide-semiconductor (CMOS) technology without any modification. For the Si-LED, wedge-shaped electrodes and needle-like tip were designed to enhance the intensity of electric field. When the Si-LED works at high forward current, the output optical power increases rapidly with the increase of forward current, which is a non-linear growth similar to exponential. To the best of our knowledge, such a phenomenon has never been reported before. Moreover, when the forward current is at 200 mA, the optical power density reaches 32.7 nW·μm 2, which is two or three orders higher than that of other ever reported forward-biased Si-LED fabricated by standard CMOS technology. In addition, the red shift of the main peak in the spectra of Si-LED was observed and analyzed, and also the light-emission mechanism of each peak in the spectra was given.